Impact of coadministration of apigenin and bone marrow stromal cells on damaged ovaries due to chemotherapy in rat: An experimental study - Athar Talebi; Nasim Hayati Roodbari; Hamid Reza Sameni; Sam Zarbakhsh (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Apigenin is a plant-derived flavonoid with antioxidative and antiapoptotic effects. Bone marrow stromal cells (BMSCs) are a type of mesenchymal stem cells (MSCs) that may recover damaged ovaries. It seems that apigenin may promote the differentiation of MSCs. Objective: The aim of this study was to investigate the effect of coadministration of apigenin and BMSCs on the function, structure, and apoptosis of the damaged ovaries after creating a chemotherapy model with cyclophosphamide in rat. Materials and Methods: For chemotherapy induction and ovary destruction, cyclophosphamide was injected intraperitoneally to 40 female Wistar rats (weighing 180-200 gr, 10 wk old) for 14 days. Then, the rats were randomly divided into four groups (n = 10/each): control, apigenin, BMSCs and coadministration of apigenin and BMSCs. Injection of apigenin was performed intraperitoneally and BMSC transplantation was performed locally in the ovaries. The level of anti-mullerian hormone serum by ELISA kit, the number of oocytes by superovulation, the number of ovarian follicles in different stages by H&E staining, and the expression of ovarian Bcl-2 and Bax proteins by western blot were assessed after four wk. Results: The results of serum anti-mullerian hormone level, number of oocytes and follicles, and Bcl-2/Bax expression ratio showed that coadministration of apigenin and BMSCs significantly recovered the ovarian function, structure, and apoptosis compared to the control, BMSC, and apigenin groups (p < 0.001). Conclusion: The results suggest that the effect of coadministration of apigenin and BMSCs is maybe more effective than the effect of their administrations individually on the recovery of damaged ovaries following the chemotherapy with cyclophosphamide in rats.